Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Determining the Possible Steps for Solving a Quadratic Equation by Completing the Square

Which are steps that could be used to solve [tex]0=9\left(x^2+6x\right)-18[/tex] by completing the square? Check all that apply.

A. [tex]18 + 81 = 9\left(x^2 + 6x + 9\right)[/tex]
B. [tex]18 + 9 = 9\left(x^2 + 6x + 9\right)[/tex]
C. [tex]18 + 36 = 9\left(x^2 + 6x + 36\right)[/tex]
D. [tex]11 = (x + 3)^2[/tex]
E. [tex]\sqrt{342} = (x + 6)^2[/tex]
F. [tex]\sqrt{99} = (x + 3)^2[/tex]


Sagot :

To solve the quadratic equation [tex]\(0 = 9(x^2 + 6x) - 18\)[/tex] by completing the square, we can follow these steps:

1. Distribute the 9 and move the constant to the other side of the equation:
[tex]\[ 0 = 9(x^2 + 6x) - 18 \][/tex]
Add 18 to both sides:
[tex]\[ 18 = 9(x^2 + 6x) \][/tex]

2. Divide by 9 on both sides to simplify:
[tex]\[ \frac{18}{9} = x^2 + 6x \][/tex]
[tex]\[ 2 = x^2 + 6x \][/tex]

3. Complete the square on the right-hand side:
To complete the square, take half of the coefficient of [tex]\(x\)[/tex] (which is 6), square it, and add it to both sides:
[tex]\[ 2 + 9 = x^2 + 6x + 9 \][/tex]
[tex]\[ 11 = (x + 3)^2 \][/tex]

4. Solve the resulting equation by taking the square root of both sides:
[tex]\[ \sqrt{11} = x + 3 \][/tex]
Therefore,
[tex]\[ x = \sqrt{11} - 3 \][/tex]
or
[tex]\[ x = -\sqrt{11} - 3 \][/tex]

Given the provided options, we can identify the steps that are valid and correspond to the correct procedure:

- [tex]\(18=9(x^2+6x)\)[/tex]
- [tex]\(18+9 = 9(x^2 + 6x + 9)\)[/tex] (completing the square using [tex]\((6/2)^2 = 9\)[/tex])
- [tex]\(11 = (x + 3)^2\)[/tex] (reflects the square completion correctly)

Therefore, the valid steps are:

[tex]\[ \boxed{18 + 9 = 9(x^2 + 6x + 9)} \][/tex]
[tex]\[ \boxed{11 = (x + 3)^2} \][/tex]